Optimum lesion set and predictors of outcome in persistent atrial fibrillation ablation: a meta-regression analysis. Issue 8 (9th May 2019) - Sau, Arunashis; Al-Aidarous, Sayed; Howard, James; Shalhoub, Joseph; Sohaib, Afzal; Shun-Shin, Matthew; Novak, Paul G; Leather, Rick; Sterns, Laurence D; Lane, Christopher; Kanagaratnam, Prapa; Peters, Nicholas S; et al.
Abstract: Aims: Ablation of persistent atrial fibrillation (PsAF) has been performed by many techniques with varying success rates. This may be due to ablation techniques, patient demographics, comorbidities, and trial design. We conducted a meta-regression of studies of PsAF ablation to elucidate the factors affecting atrial fibrillation (AF) recurrence. Methods and results : Databases were searched for prospective studies of PsAF ablation. A meta-regression was performed. Fifty-eight studies (6767 patients) were included. Complex fractionated atrial electrogram (CFAE) ablation reduced freedom from AF by 8.9% [95% confidence interval (CI) −15 to −2.3, P  = 0.009). Left atrial appendage [LAA isolation (three study arms)] increased freedom from AF by 39.5% (95% CI 9.1–78.4, P  = 0.008). Posterior wall isolation (PWI) (eight study arms) increased freedom from AF by 19.4% (95% CI 3.3–38.1, P  = 0.017). Linear ablation or ganglionated plexi ablation resulted in no significant effect on freedom from AF. More extensive ablation increased intraprocedural AF termination; however, intraprocedural AF termination was not associated with improved outcomes. Increased left atrial diameter was associated with a reduction in freedom from AF by 4% (95% CI −6.8% to −1.1%, P  = 0.007) for every 1 mm increase in diameter. Conclusion : Linear ablation, PWI, and CFAE ablation improves intraprocedural AF termination, but such termination does not predict better long-term outcomes. Study arms including PWI or LAA isolation in the lesion set were associated with improved outcomes in terms of freedom from AF; however, further randomized trials are required before these can be routinely recommended. Left atrial size is the most important marker of AF chronicity influencing outcomes.